Health risk behaviour attitude towards physical activity among young university students - W. Vinu; Ayona Eldos; Dilshith Azeezul Kabeer; Anbalagan P; Praveen A; Manibharathi G; John M (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Adolescence and early adulthood represent a critical period that shapes long-term health outcomes and lays the foundation for a healthy and productive life. Understanding the influence of health risk behaviors on physical activity and dietary habits is essential for targeted public health interventions.